Three‐channel electrical impedance spectroscopy for field‐scale root phenotyping. Issue 1 (30th June 2021) - Peruzzo, Luca; Liu, Xiuwei; Chou, Chunwei; Blancaflor, Elison B.; Zhao, Haijun; Ma, Xue‐Feng; Mary, Benjamin; Iván, Veronika; Weigand, Maximilian; Wu, Yuxin
Abstract: Electrical impedance spectroscopy has long been considered a promising technique for noninvasive, in‐situ root investigation because of its sensitivity to anatomy and physiology. However, the complexity of the root system and its coupling with stem and soil have hindered the signal interpretation and methodological upscaling to field applications. This study addresses these key issues by introducing three‐channel acquisitions and their interpretation through Cole–Cole fitting. This solution could successfully decouple the impedance response of stem, roots, and soil, as well as provide convenient parametrization and comparison of their impedance signals. The methodological solution was tested on 80 wheat ( Triticum aestivum L.) and 10 pecan [ Carya illinoensis (Wangenh.) K. Koch] plants, the first extensive and field investigation. The investigation provided evidence of (a) proximal current leakage in herbaceous root systems, extending recent laboratory results and previous indirect field studies. (b) Major role of the plant stem, which has been a substantial concern raised in numerous studies. (c) Minor contribution from the soil, addressing the doubts on the comparability of results obtained in different soil conditions. All together, these evidences lead to indirect correlations between impedance signals and root traits. The explored solution is expected to support the adoption of the impedance spectroscopy, in line with the diffusion of multichannel impedance meters and growing interest in root physiology and phenotyping. Core Ideas: Three‐channel and Cole–Cole fitting can target the impedance response of the root system. First field scale impedance spectroscopy campaign, 80 wheat and 10 pecan plants. Dominant role of stem and proximal roots on the impedance response. Indirect correlation between impedance signals and root traits. Minor soil influence even in clayey soils.